Clustering entrepreneurship aspirations: innovation, growth and international orientation of activities - Nunes, Alcina (2014)
It is sometimes argued that nations differ in their underlying entrepreneurial spirit. So, in recent years, more researchers started being interested in the analysis of entrepreneurship across countries and regions. Some of the international literature on the subject recognises that regional variation in entrepreneurship is significant and persistent, and often even exceeds national differences. Associated with entrepreneurship comes the concept of innovation. Indeed the seminal work of Schumpeter establishes conceptually the entrepreneur as an innovator. Nowadays the belief that innovation has an important role in the international entrepreneurial activity rate has been theoretical and empirically analysed/tested. Innovation allows the creation of new firms and/or ensures the survival of the existing ones. In both cases, it generates growth. Applying the statistical technique of cluster analysis to a dataset gathered by the Global Entrepreneurship Monitor (GEM) and that includes, in 2010, 59 countries; this paper intends to group countries into clusters regarding their entrepreneurial activity and the aspirations of national entrepreneurs concerning innovation, business growth and international orientation of their activities. It aims to identify and characterise different international entrepreneurial aspiration profiles. Note, however, that cluster analysis should be considered an exploratory data-analysis technique that is intended largely for generating rather than testing hypothesis. So this paper aims to divide the set of analysed countries in groups that share similar aspirations regarding the previous mentioned entrepreneurial aspirations. This is particularly important not only because the achievement of a relevant national entrepreneurship rate depends on the social and economic business environment but also because, despite the international attention given to entrepreneurship, it is not known if it is a global phenomenon or if there are particular regions where the entrepreneurial activity is characterised by special patterns of entrepreneurship aspirations. The use of an international comparable entrepreneurship unique dataset allows cross-country comparisons and therefore to reach the proposal goal.